Impact of Budget Waste on Infractructure Development in Sibolga - Ayu Kurnia Sari; Hendra Saputra; Ku Halim Bin Ku Arifin; Aulia Aulia (International Journal of Social Service and Research, 2022)
The background of this research is that a lot of government budget is used for infrastructure development. However, the infrastructure development in the district government of Sibolga, North Sumatra, is very uneven and poor in infrastructure development. This also results in the existing budget being wasted and not even in line with the government's expectations. Center and the local community. For example, road construction is very bad. Not to mention the construction of schools that are very far away for each sub-district in one sub-district and the lack of school facilities. The lack of infrastructure development facilities and infrastructure in Sibolga is very minimal. Local revenue is relatively high because the effort produces a lot of natural resources. As a result, this research wants to see whether there is an impact of wasting development budget on infrastructure in Sibolga. From the study results, it can be said that the impact of budget leakage on the city of Sibokga is classified as non-existent. This is because the city of Sibolga is the smallest in Indonesia. so that the amount of the PAD budget is only Rp. 609,443,390,610. The lack of budget for infrastructure in the city of Sibolga does not affect this because the city of Sibolga has a low PAD compared to other cities in the province of North Sumatra